Antibody Response to the BNT162b2 mRNA COVID-19 Vaccine in Subjects with Prior SARS-CoV-2 Infection - Gobbi, Federico; Buonfrate, Dora; Moro, Lucia; Rodari, Paola; Piubelli, Chiara; Caldrer, Sara; Riccetti, Silvia; Sinigaglia, Alessandro; Barzon, Luisa (Viruses, 2021)
Although antibody levels progressively decrease following SARS-CoV-2 infection, the immune memory persists for months. Thus, individuals who naturally contracted SARS-CoV-2 are expected to develop a more rapid and sustained response to COVID-19 vaccines than naïve individuals. In this study, we analyzed the dynamics of the antibody response to the BNT162b2 mRNA COVID-19 vaccine in six healthcare workers who contracted SARS-CoV-2 in March 2020, in comparison to nine control subjects without a previous infection. The vaccine was well tolerated by both groups, with no significant difference in the frequency of vaccine-associated side effects, with the exception of local pain, which was more common in previously infected subjects. Overall, the titers of neutralizing antibodies were markedly higher in response to the vaccine than after natural infection. In all subjects with pre-existing immunity, a rapid increase in anti-spike receptor-binding domain (RBD) IgG antibodies and neutralizing antibody titers was observed one week after the first dose, which seemed to act as a booster. Notably, in previously infected individuals, neutralizing antibody titers 7 days after the first vaccine dose were not significantly different from those observed in naïve subjects 7 days after the second vaccine dose. These results suggest that, in previously infected people, a single dose of the vaccine might be sufficient to induce an effective response.